LncRNA CRNDE is a biomarker for clinical progression and poor prognosis in clear cell renal cell carcinoma. Issue 12 (20th August 2018) - Ding, Chenguang; Han, Feng; Xiang, Heli; Xia, Xinxin; Wang, Yuxiang; Dou, Meng; Zheng, Jin; Li, Yang; Xue, Wujun; Ding, Xiaoming; Tian, Puxun
Abstract: Colorectal neoplasia differentially expressed (CRNDE) served as an oncogenic long noncoding RNA (lncRNA) to be involved in the initialization and development of human cancers. However, the clinical significance and biological function of CRNDE in clear cell renal cell carcinoma (ccRCC) was not fully understood. In our study, we found CRNDE levels were increased in ccRCC tissue specimens and cell lines, and corrected with advanced clinical stage, large tumor size, lymph node metastasis, distant metastasis, and poor pathological grade in patients with ccRCC. Furthermore, levels of CRNDE were negatively correlated with overall survival of patients with ccRCC, and high‐expression of CRNDE was an independent poor prognostic factor for patients with ccRCC. Moreover, loss‐of‐function and gain‐of‐function approaches showed CRNDE‐enhanced ccRCC cell migration and invasion through modulating EMT‐associated genes. In conclusion, CRNDE acts as an oncogenic lncRNA in ccRCC. Abstract : Colorectal neoplasia differentially expressed (CRNDE) overexpression is associated with clinical progression, and served as an independent prognostic marker for patients with clear cell renal cell carcinoma (ccRCC). CRNDE‐enhanced ccRCC cell migration and invasion through modulating EMT‐associated genes.